PENYULUHAN PEMBERDAYAAN MASYARAKAT DALAM PENCEGAHAN STUNTING DESA AJIJULU, KABUPATEN KARO - Siahaan, Jekson Martiar; Silitonga, Hendrika Adriana; Lim, Hadyanto; Pasaribu, Sumihar M. R.; Tarigan, Menang Bastanta; Jamnasi, Juli; Sinatra, Jadeny; Simanjuntak, Salomo Garda Utama; Sembiring, Budi Darmanta; Pakpahan, Edwin Anto; Hutagalung, Sanggam B.; Sinurat, Suryati; Br. T. Tambun, Gita Sradha; Hakim, Enggrek Pelita (Universitas Methodist Indonesia, 2023)
Community Service (PKM) conducted by the Faculty of Medicine at the Indonesian Methodist University provides counseling on stunting prevention. PKM was held on April 14-16 2023 in Ajijulu Village, Tigapanah District, Karo Regency, North Sumatra. Lectures, discussions and motivations are used as orientation methods. Question and answer discussions were held with the aim of gaining insight, understanding and solutions to solve the problems and limitations faced by the local community. The results of the PKM suggestions and research are very effective, considering that there are still many people who are ignorant of stunting prevention. This counseling increases public awareness about stunting prevention. Residents of Ajijulu must be aware and know the importance of preventing stunting, starting from the time of pregnancy and the first 1000 days of life for toddlers.